2009
DOI: 10.1614/ws-09-056.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Resistance to ALS-Inhibitor Herbicides in Greater Beggarticks

Abstract: Soybean is a major crop cultivated in Brazil, and acetolactate synthase (ALS)-inhibiting herbicides are widely used to control weeds in this crop. The continuous use of these ALS-inhibiting herbicides has led to the evolution of herbicide-resistant weeds worldwide. Greater beggarticks is a polyploid species and one of the most troublesome weeds in soybean production since the discovery of ALS-resistant biotypes in 1996. To confirm and characterize the resistance of greater beggarticks to ALS inhibitors, whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
5
35
0
1
Order By: Relevance
“…For the CYPIR biotypes with high cross-resistance to ALS-inhibiting herbicides, Riar et al (2015) identified the Trp-574 alteration in the enzyme gene. In a biotype of Bidens subalternans, this mutation was also responsible for the cross-resistance to ALS inhibitors, conferring a high level of resistance (Lamego et al, 2009b). Brosnan et al (2015) observed that the substitution of the amino acid alanine (Ala-205 -Fen) also confers a broad spectrum of resistance to ALS inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…For the CYPIR biotypes with high cross-resistance to ALS-inhibiting herbicides, Riar et al (2015) identified the Trp-574 alteration in the enzyme gene. In a biotype of Bidens subalternans, this mutation was also responsible for the cross-resistance to ALS inhibitors, conferring a high level of resistance (Lamego et al, 2009b). Brosnan et al (2015) observed that the substitution of the amino acid alanine (Ala-205 -Fen) also confers a broad spectrum of resistance to ALS inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research with ALS-resistant BIDPI have demonstrated cross-resistance to different chemical groups including imidazolinones and sulfonylureas (chlorimuron, metsulfuron, nicosulfuron and imazethapyr) (Christoffoleti, 2002). In BIDSU, the mechanism of resistance to ALS inhibitors involves a point mutation in the ALS gene (Trp 574 Leu, Phe 116 Leu or Phe 149 Ser), which confers high resistance level (RF=166) (Lamego et al, 2009). Considering that this is the first report of resistance to photosystem II inhibitors in BIDPI, the mechanisms that confer such resistance is still to be investigated.…”
Section: Resistance To Imazethapyrmentioning
confidence: 99%
“…Resistance to herbicides that inhibit the ALS enzyme has been attributed to amino acid alteration(s) in the ALS protein. Lamego et al (2009) Many grain-producing farmers of West-Central and Southern regions of Brazil practice soybean-corn double cropping. Before glyphosate-resistant (GR) soybean was introduced in Brazil in 2006, the recurrent use of ALS inhibitors in soybean and of PSII inhibitors in corn was the primary driver for resistance selection.…”
Section: Introductionmentioning
confidence: 99%
“…Blockage of the electron transport chain by these herbicides results in depletion of ATP and NADPH synthesis, and thereby CO 2 fixation, leading to cellular damage by oxidative stress [7] [8]. Acetolactate synthase-inhibitors are one of the most commonly used type of herbicides for controlling wide spectrum of weeds in agronomic crops [9]. These herbicides inhibit ALS, which catalyzes the biosynthesis of branched-chain amino acids leucine, valine, and isoleucine [10].…”
Section: Introductionmentioning
confidence: 99%